PERAN TAMAN PENDIDIKAN AL-QUR”AN NURUL YAQIN DALAM MEMBINA AKHLAK SANTRI DI KELURAHAN AIR LINTANG MUARA ENIM - Andika Agustian; Ifnaldi (Indonesian Journal of Islamic and Social Science, 2024)
In Islam, the concept of morality, or moral and ethical character, occupies a central position in the teachings of Islam. The concept of moral education in Islam not only emphasizes the aspects of ritual worship, but also emphasises the importance of behavior and attitudes that reflect moral values. In Islamic view, akhlak is a strong foundation for guiding individuals in living everyday life and interacting with fellow human beings. Islam as a perfect doctrine provides guidelines and norms that are clearly related to morality. The Prophet (peace and blessings of Allah be upon him) was a prophet of the prophet Muhammad (salla Allahu alihi wa sallam). How is the concept of the creation of a religion in Islam then how is the model of creation in the institutions of Islamic education and the purpose of the problem to know the concepts of creations in Islam, To know how is a model of the Creation of an Religion in Islamic educational institutions